Antecedents and service contact in an observational study of 242 suicide deaths in middle-aged men in England, Scotland and Wales, 2017 - Nav Kapur; Saied Ibrahim; Jane Graney (BMJ Public Health)
Introduction Middle-aged men are the demographic group at highest risk of dying by suicide. We conducted a national study of deaths by suicide in men in mid-life to investigate the stresses they face before they take their lives and their contact with services that could be preventative.Methods This study is a detailed descriptive examination of suicide in a sample of men aged 40–54 who died by suicide in England, Scotland and Wales in 2017, based on national mortality data. We extracted information on the antecedents of suicide from official investigations, mainly coroner inquests and police death reports.Results In 2017, there were 1516 suicides by middle-aged men, representing 25% of all suicide deaths. Of the 288 suicide deaths in middle-aged men randomly selected for review, we obtained data about antecedents on 242 (84%). Many were unmarried (161, 67%). We found a complex pattern of stresses and recent adversity before suicide including economic adversity (139, 57%), physical ill-health (125, 52%), self-harm (106, 44%), alcohol and/or drug misuse (119, 49%), and bereavement (82, 34%; including by suicide, 14, 6%). Most men (220, 91%) had known contact with healthcare, justice system or other support services—67% (n=162) in the previous 3 months, 38% (n=91) in the previous week. Contact with multiple agencies was reported for 17% of men.Conclusions A mix of long-standing and recent risks contribute to suicide risk in men in mid-life. Economic stresses, including unemployment, financial and housing problems, are particularly important factors in this group. Contrary to our expectations, most men were in contact with support services. Economic support (especially at a time of severe economic pressure), addressing isolation, joint working with the voluntary sector, and addressing specific stresses, such as bereavement, may help reduce risk.